2016
DOI: 10.1515/auoc-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of aquaculture mussels (M. galloprovincialis) from the Black Sea, Bulgaria

Abstract: In recent years black mussels are one of the most commercially important species from the Bulgarian Black Sea. The marine mollusks are valuable healthy food, low in calories and fats and high in proteins. They are a major dietary source of fat soluble pigments - astaxanthin, carotenoids and polyunsaturated fatty acids (PUFA). To our knowledge the information about the nutritional quality of mussels from the Bulgarian Black Sea waters, based on chemical composition, fat soluble pigments, cholesterol and PUFA co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
(33 reference statements)
2
7
0
1
Order By: Relevance
“…The present results are in accordance with some previous investigations [23,26,28] of farmed Mediterranean and Black Sea mussels. Some authors [25] report significantly lower PUFA and n3 PUFA values for mussels from Mar Grande of Taranto (7.55-11.16%) in comparison to our findings.…”
Section: Biological Resources Of Water 188supporting
confidence: 94%
See 3 more Smart Citations
“…The present results are in accordance with some previous investigations [23,26,28] of farmed Mediterranean and Black Sea mussels. Some authors [25] report significantly lower PUFA and n3 PUFA values for mussels from Mar Grande of Taranto (7.55-11.16%) in comparison to our findings.…”
Section: Biological Resources Of Water 188supporting
confidence: 94%
“…Thus, in accordance with [48], the analyzed farmed Black Sea mussels can be classified as high in omega-3 fatty acids regardless of the season. In our previous study [28], the reported results for EPA + DHA contents of Black Sea mussels are lower (0.45 g/100 g). Comparable information in literature for seasonal changes in long-chain n3 PUFAs contents in Black Sea mussel edible tissues was not found.…”
Section: Assessment Of the Nutritional Quality Of The Mussel Lipidsmentioning
confidence: 72%
See 2 more Smart Citations
“…[33,34,37,[39][40][41] Those fatty acids occurring in the highest amounts were myristic acid (C14:0, 2.32 AE 0.12 mg 100 g À1 for Soxhlet to 184.62 AE 3.47 mg 100 g À1 for Bligh and Dyer), palmitic acid (C16:0, 17.78 AE 0.16 mg 100 g À1 for Soxhlet to 1164.70 AE 9.64 mg 100 g À1 for Bligh and Dyer), palmitoleic acid (C16:1, 3.37 AE 0.05 mg 100 g À1 for Soxhlet to 378.78 AE 3.47 mg 100 g À1 for Bligh and Dyer), stearic acid (C18:0, 6.95 AE 0.24 mg 100 g À1 for Soxhlet to 334.06 AE 1.93 mg 100 g À1 for Bligh and Dyer), oleic acid (C18:1n-9, 7.54 AE 0.61 mg 100 g À1 for Soxhlet to 1638.9 AE 4.45 mg 100 g À1 for Bligh and Dyer), cis-vaccenic acid (18:1n-7, 2.11 AE 0.04 mg 100 g À1 for Soxhlet to 269.43 AE 0.77 mg 100 g À1 for Bligh and Dyer), linoleic acid (C18:2n-6, 0.88 AE 0.10 mg 100 g À1 for Soxhlet to 58.63 AE 2.70 mg 100 g À1 for Bligh and Dyer), erucic acid (C22:1n9, 1.29 AE 0.09 mg 100 g À1 for Soxhlet to 125.11 AE 4.24 mg 100 g À1 for UAE), eicosapentaenoic acid (EPA, C20: 5n3, 2.05 AE 0.29 mg 100 g À1 for Soxhlet to 278.15 AE 3.09 mg 100 g À1 for Bligh and Dyer), decosahexaenoic acid (DHA, C22: 6n3, 10.82 AE 0.38 mg 100 g À1 for Soxhlet to 454.06 AE 11.48 mg 100 g À1 for UAE). These results are in agreement with previous studies on fatty acid profiles of European eel extracted from Bligh and Dyer, [31,42] from Folch method, [43] brushtooth lizardfish from Bigh and Dyer, [38] red mullet from Bligh and Dyer, [32,34,38,39,44] striped redmullet (or surmullet) from Bligh and Dyer, [33] striped redmullet from Folch method, [37] common pandora extracted from Bligh and Dyer method, [45] from Folch method, [46] from Soxhlet method, [39] brushtooth lizardfish from Bligh and Dyer, [17,41] and goldband goatfish from Bligh and Dyer, [33] extracted according to Lovell [36] method. [35] Like lipid content, the fatty acid composition of fish species is not constant and it varies depending on many ecological and morphological factors such as species, season, location, diet, lifestage, and age of the fish, which have major www.advancedsciencenews.com www.ejlst.com impacts on the nutrient levels of fish and even vary broadly within species and between species [47] Previous report...…”
Section: Fatty Acid Compositionsupporting
confidence: 93%